2015
DOI: 10.5194/cp-11-915-2015
|View full text |Cite
|
Sign up to set email alerts
|

Thermal evolution of the western South Atlantic and the adjacent continent during Termination 1

Abstract: Abstract. During Termination 1, millennial-scale weakening events of the Atlantic meridional overturning circulation (AMOC) supposedly produced major changes in sea surface temperatures (SSTs) of the western South Atlantic, and in mean air temperatures (MATs) over southeastern South America. It has been suggested, for instance, that the Brazil Current (BC) would strengthen (weaken) and the North Brazil Current (NBC) would weaken (strengthen) during slowdown (speed-up) events of the AMOC. This antiphase pattern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 98 publications
3
36
0
Order By: Relevance
“…Considering the age uncertainties, the most conspicuous change observed over the YD was a pronounced salinity decrease (Figure c). That finding is also in line with other records from the western subtropical South Atlantic showing diminished salinity both northward (25°S) (Pivel et al, ) and further south (32°S) to our study area (Chiessi et al, ) during the YD. It is likely that shifts in the interhemispheric export of salt throughout the last deglaciation (Chiessi et al, ; Pivel et al, ) fueling the AMOC recovery toward the Holocene (Figure j) would have strongly contributed to such anomalous salinity decrease recorded along the YD.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Considering the age uncertainties, the most conspicuous change observed over the YD was a pronounced salinity decrease (Figure c). That finding is also in line with other records from the western subtropical South Atlantic showing diminished salinity both northward (25°S) (Pivel et al, ) and further south (32°S) to our study area (Chiessi et al, ) during the YD. It is likely that shifts in the interhemispheric export of salt throughout the last deglaciation (Chiessi et al, ; Pivel et al, ) fueling the AMOC recovery toward the Holocene (Figure j) would have strongly contributed to such anomalous salinity decrease recorded along the YD.…”
Section: Discussionsupporting
confidence: 94%
“…The currents are labeled as AC‐Agulhas Current, ACC‐Antarctic Circumpolar Current, BC‐Brazil Current, BCC‐Brazilian Coastal Current, BGC‐Benguela Current, MC‐Malvinas Current, SAC‐South Atlantic Current, SEC‐South Equatorial Current. The location of the marine sediment core investigated in this study, as well as of some archives discussed here are shown: (1) GeoB2107‐3 (this study), (2) GL‐1090 (Lessa et al, ), (3) BCCF06‐03 (Souto et al, ), (4) GL‐74 (Portilho‐Ramos et al, ), (5) GeoB6211‐2 (Chiessi et al, ), and (6) Botuverá Cave (Wang et al, ). The satellite images show the core site location (black and white circle) and the mesoscale surface circulation off Cape Santa Marta (CSM), defined by the meandering flow of the Brazil Current (BC): (b) the infrared satellite image (AVHRR/NOAA) depicts the development of the Santa Marta cyclonic vortex delineated by a thermal contrast in °C (color shading) between the BC and the Brazilian Coastal Current (BCC); (c) the ocean color satellite image (VIIRS‐SNPP/NOAA) depicts the development of Santa Marta cyclonic vortex delineated by the surface chlorophyll a concentration in mg/m 3 (color shading) mirroring phytoplankton bloom and primary productivity.…”
Section: Regional Settingmentioning
confidence: 56%
See 3 more Smart Citations